The autobiographical device between transformational experiential research and pedagogy of the imaginary - Orazio Maria Valastro (University of Bologna, 2017)
This paper proposes an analysis of the pedagogic device which from 2005 accompanies groups of the adults to experience the imaginary in the writing of self, of the courses annuals structured and organized into community spaces in the framework of the activities Ateliers of the autobiographical imaginary of the voluntary organization The stars in your pocket, comparing the experiential and existential research of the participants with the experience of empirical research that has guided the development of a knowledge and an educational practice able to accept and recognize the experience lives of women and men.